Hybrid conceptual model for assessing quality, production and satisfaction (SQual4Agri), in Agricultural Production Units, in Cape Verde - Simões, E.; Saraiva, M.; Basch, G.; Pires, A. R.; Rosa, A.; Chaleta, E. (Sustainability, 2021)
In Cape Verde, small family farming production suffers continuously from limited essential resources such as water and soil for a steady development. This situation is further aggravated by the lack of financial resources. We have developed a hybrid and multidimensional conceptual model for improvement of those small farming units by bringing together concepts of quality management, farmers’ satisfaction evaluation and production capabilities. The model we have built was the result of an inquiry based on Focus Group study with 15 farmers and it was carried out in 2019. We name the model as SQual4Agri and this is a step toward improvement in small family based agricultural organization, namely in productivity, responsibility sharing, communication and quality management.